Memórias e histórias de Quilombo no Ceará - Dantas, Simone Maria Silva (2009)
In this research, Memories and stories of quilombos in Ceará, we first analyze the means to enter the quilombo areas in an intimate manner, which was possible due to the value given to empiric data. Therefore, it was possible to enter the territories and to rely on the cultural heritage and the subjectivities. In order to achieve that goal, we specifically used memories, talks, and photographs as tools in the remaining quilombo communities in Minador, Bom Sucesso and Cumbe. We managed to unearth specificities and we were challenged to gain access to factors which are silenced or denied in Ceará historiography, and were thus able to witness the disturbing impact for the social-historical African descendants in Ceará. These actors deserve to and must give a detailed account of their stories from their own perspective. It is important to acknowledge their own theories about what is the meaning of the quilombo remains and reminiscences and how these social historical actors gather in the various contexts where they are included or, if we may say, excluded. Although being a negro in Ceará is not synonymous with being a descendant of an ex-slave, the essence of the idea of slavery remains in the skin of the Blacks and Pardos from that state, which brings serious harm to their quotidian life. There is a necessity to revisit the points of view and the gaps in the historiography of Ceará in order for the historical exclusion of the Blacks to lose their space in the historiography records. The studies conducted in these three remaining quilombo communities highlight points of view and gaps which deny or marginalize the Blacks and Pardos in their relevance in constructing the historical process of this state. The need to include Blacks and Pardos in a responsible manner and with social and historical justice is visible for those who do not intend to close their eyes to the social, economic and cultural way of life in Ceará